Re-Use of Date Palm Wastes to Improve Aging of Composite Concrete System - Abas, Falak O. (Iraqi Journal of Science, 2020)
The presented research aims to manipulate and improve the aging behaviors of concrete composite systems by employing ecologically safe date palm (seeds and husks) waste as a filler. In addition, optimized workability, durability, and erosion resistance properties for the new material were investigated.The experimental work included the application of different mixing ratios (50/50, 30/70, and 70/30) of husk date/ date seeds to study the enhanced physicochemical behaviors and erosion resistant of bio-waste-concrete composite system exposed to severe temperature conditions (50 ÂºC) for a time period of 25 days. Optimum results were observed for samples reinforced with the natural filler with a ratio of 50/50 in comparison to the base samples.In conclusion, good resistance to erosion and creeping thickness appeared at optimum conditions of 250 Î¼m particle size. Also, higher reaction compatibility and less pores between particles were observed, which improved all physical and chemical properties as depicted by SEM images.